Pengembangan Bank Soal Interaktif "Adaptasi Makhluk Hidup" Berbasis Quizlet Untuk Evaluasi Pembelajaran IPA Kelas 6 SD - Rahmalia Ayu Isnaini; Ika Putra Viratama (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
Science learning in elementary schools requires evaluation strategies that are able to measure conceptual understanding while enhancing students’ motivation and engagement. One of the contextual science topics in Grade VI that requires visualization is the adaptation of living organisms. However, science learning evaluation is still dominated by conventional assessment instruments that are less varied and have not optimally utilized digital technology. This study aims to examine the development of an interactive question bank based on Quizlet as an alternative assessment tool for science learning on the topic of adaptation of living organisms in Grade VI elementary schools. This study employs a qualitative approach using a literature review method by analyzing relevant scientific articles, books, and educational policy documents. The results of the review indicate that a Quizlet-based interactive question bank has the potential to improve the quality of learning evaluation through the use of varied and interactive questions accompanied by immediate feedback. The use of Quizlet also supports student-centered learning and aligns with the principles of meaningful assessment promoted in the Merdeka Curriculum.